Brain Drain and Fiscal Competition. A theoretical model for the Europe - Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
In this paper we study Brain Drain (BD) and Fiscal Competition (FC) in a unified framework for the European Union (EU) specific context. Potential mobility of educated workers can increase the degree of FC through taxation or the provision of public education. An increase in FC can be caused by competition among different jurisdictions that aim to attract educated workers. When the importance of FC increases, then the European States may employ FC as a new policy tool. First, we analyze FC and BD with reference to EU regions. In this instance, the EU may find incentive to control the interactions between BD and FC in order to coordinate fiscal policies and/or the provision of public goods as education. Second, we furthermore consider the entry of new state inside the EU. The absence of coordination implies that, in addition to the FC, a "migration competition" may be generated in EU, where the region inside the union try to attract educated workers of the new entry. We derive the conditions which BD leads to a decrease (increase) in welfare and growth for new entry country.
Keywords: 330